(3TeS GdYdhe hOhGA cdGe GdYQH ef Gdcdhes - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s ((3Ydi Hf fThGf (B" (3GHf GdeDda (B" s)
(3ChdgG (B:s
(3Ghd GdcJGH s
(3BNQgG (B:s
(3Edi BNQ GdMGA s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B86s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B16 - (3U (B359 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs